Molecular epidemiology of toxigenic Clostridioides difficile isolates from hospitalized patients and the hospital environment in Dhaka, Bangladesh. (February 2020) - Sofjan, Amelia K.; Islam, Mohammad Aminul; Halder, Kakali; Kabir, Nayel D.; Saleh, Ahmed Abu; Miranda, Julie; Lancaster, Chris; Begum, Khurshida; Alam, M. Jahangir; Garey, Kevin W.
Abstract: Epidemiology of Clostridioides difficile (syn. Clostridium difficile ) infection (CDI) in Bangladesh is poorly understood. This study assessed the epidemiology of CDI in hospitalized patients and hospital environmental contamination of toxigenic C. difficile at two large urban Bangladesh hospitals. This 12-month prospective observational cohort study collected stool samples from adults with diarrhea and recent antimicrobial exposure during 2017. Environmental samples were collected by swabbing surfaces of hospital common areas. Samples underwent toxigenic culture. C. difficile isolates were tested for toxins A and B and PCR-ribotyped. Of 208 stool samples, 18 (8.7%) were positive for toxigenic C. difficile . Of 400 environmental samples, 45 (11%) were positive for toxigenic C. difficile. Ribotypes present in ≥10% of stool isolates were 017 (38%), 053–163 (13%), and a novel ribotype (FP435 [13%]). Common ribotypes in environmental isolates were 017 (22%), 053–163 (11%), 106 (24%). This is the first report describing current epidemiology of CDI in at risk hospitalized adult patients in Bangladesh. Highlights: Epidemiology of toxigenic C. difficile in Bangladesh is poorly understood. 9% of 208 diarrheal stool samples from hospitalized adults had toxigenic C. difficile . Most common ribotype in stool toxigenic C. difficile isolates was 017 (38%). 11% of 400 hospital environmental samples were positive for toxigenic C. difficile . Common ribotypes in environmental toxigenic C. difficile isolates were 017 and 106.